2021
DOI: 10.22190/fume201212010p
|View full text |Cite
|
Sign up to set email alerts
|

The Ceramic Modular Head Improvement in the Design of a Total Hip Replacement

Abstract: For the first time, a design of a modular ceramic ball head of a total hip joint replacement (THR) friction pair has been developed, which has the properties of a metal in conjunction with the stem neck and the properties of a ceramics on bearing surface of the pair. This is achieved by creating a low-cost, low-toxic, durable fixed connection of the head made of alumina or zirconia ceramics and the titanium-based alloy sleeve to obtain a brazed joint that is efficient in human synovial fluid. With the help of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The performed finite element analysis of the head design with no sleeve showed that the greatest stress es and strains in the ceramics were at the outlet in the head. In the presence of a sleeve the zone with maximum stresses and strains shifted to the area where the ceramics are practically the thickest, and the values of stresses and strains reduced by more than 2 times [77], on the basis of which the thicknesses of the sleeve and ceramics 1 were select ed, also considering the requirements of medical standards. To create a fixed joint be tween the ceramic element of the head and the titanium alloy sleeve, the technology of their brazing was developed, as well as the solder itself with the required biocompatibility index [78].…”
Section: Resultsmentioning
confidence: 99%
“…The performed finite element analysis of the head design with no sleeve showed that the greatest stress es and strains in the ceramics were at the outlet in the head. In the presence of a sleeve the zone with maximum stresses and strains shifted to the area where the ceramics are practically the thickest, and the values of stresses and strains reduced by more than 2 times [77], on the basis of which the thicknesses of the sleeve and ceramics 1 were select ed, also considering the requirements of medical standards. To create a fixed joint be tween the ceramic element of the head and the titanium alloy sleeve, the technology of their brazing was developed, as well as the solder itself with the required biocompatibility index [78].…”
Section: Resultsmentioning
confidence: 99%
“…With the participation of this work's authors, a technology for soldering these materials was developed, which provides a connection with high tensile, compressive and shear strength [71]. As a result, it became possible to develop a modular femoral head, the general view and 3D model of which are shown in Figure 4.…”
Section: Improving the Components Design For Total Hip Arthroplastymentioning
confidence: 99%
“…In addition to the characterization of the brazed seam, investigations on the final cubic ceramic head with the titanium insert are required in the next steps in order to verify, for example, the damping properties of the titanium insert, as already shown by simulation [27]. For this purpose, digital image correlation (DIC) or local strain measurements with strain gauges should be used, as already shown in combination for brazed steel joints in [28].…”
Section: Futher Investigationsmentioning
confidence: 99%